Antiulcer potential of Sapium indium aqueous extract: Towards the development of halal pharmaceutical ingredient with gastroprotective property - Md Tohid, Siti Farah; Darnis, Deny Susanti; Bakhtiar, M. Taher; Ismail, F. I.; Balan, T.; Zakaria, Zainul Amiruddin (2014)
With the growing number of population suffering of gastro-related diseases such as ulcer and gastritis, the need to find novel halal pharmaceutical ingredients with gastroprotective activity is also increasing significantly, especially among the Muslim population. The conventional antiulcer drugs are over shaded with unwanted side effects. Plant kingdom is regarded as one of the valuable source to fulfill such need. One of the plants that currently caught our attention is Sapium indicum. Therefore, based on the traditional use of S. indicum to relieve pain and to heal wound, as well as the scientifically reported antimicrobial, antinociceptive and antioxidant properties, this study was intended to evaluate the antiulcer potential of S.indcium aqueous extract (SIAE) using established ethanol and indomethacine-induced models, followed by pylorus ligation model for antiulcer mechanisms. The SIAE was prepared at doses of 25, 125 and 250 mg/kg, together with distilled water (negative control) and ranitidine 100 mg/kg (positive control). In ethanol-and indomethacine-induced ulcer models, all doses of SIAE showed reduction in ulcer area formation with 250mg/kg exhibited the best activity with approximately 85.8% and 82% protection respectively when compared to the control group. This is supported by histological findings which showed reduction in epithelial and glandular disruption, congestion, oedema and hemorrhage score with the absence of necrosis and erosion when compared to negative control. The pylorus ligation study also confirmed that SIAE ability to retard ulcer formation by reducing the free and total acidity of gastric secretion in the rats, and enhancement of the gastric mucosal defence action by increased mucus secretion amount. In conclusion, the study suggested that SIAE illustrated good gastroprotective property, which will become s strong basis to develop Halal S.indicum-based pharmaceutical ingredients with gastroprotective property.